Legal And Institutional Framework For Promoting Oil Pipeline Security In Nigeria - Okafor, Amalachukwu; Olaniyan, Ayobami (Journal of Sustainable Development Law and Policy, 2025)
Oil pipelines are no ordinary assets, and their security is of utmost importance especially in a country like Nigeria where oil pipelines are the major means of transporting crude oil. Nigeria relies on this means of transportation, which has been the victim of various physical attacks over the years by vandals and militant groups. This has affected the transportation of crude oil, which isthe most important resource sustaining the Nigerian economy, putting it in jeopardy. This article appraises the efficacy of relevant Nigerian legislation providing for oil pipelines security; highlights the weaknesses of the current regulatory arrangement, and suggests legal reforms to make oil transportation through pipelines efficient, effective and secure in Nigeria. These reforms include the need to have a comprehensive legislation on oil pipeline security; the need to review relevant legislation providing for the security of oil pipelines in Nigeria; proper funding of the security agencies saddled with the overall responsibility for managing as well as safeguarding the pipelines to ensure their productivity; and overhauling the entire security apparatus put in place to protect oil pipelines in Nigeria by having a sustainable and strategic approach to dealing with oil pipeline insecurity.